Cytoskeleton dynamics are necessary for early events of lateral root initiation in Arabidopsis - Vilches-Barro, Amaya; Ruiz Duarte, Paola; Bald, Lotte; Louveaux, Marion; Born, Patrick von; Denninger, Philipp; Maizel, Alexis (Current biology, 2019)
Summary - How plant cells re-establish differential growth to initiate organs is poorly understood. Morphogenesis of lateral roots relies on the asymmetric cell division of initially symmetric founder cells. This division is preceded by the tightly controlled asymmetric radial expansion of these cells. The cellular mechanisms that license and ensure the coordination of these events are unknown. Here, we quantitatively analyze microtubule and F-actin dynamics during lateral root initiation. Using mutants and pharmacological and tissue-specific genetic perturbations, we show that dynamic reorganization of both microtubule and F-actin networks is necessary for the asymmetric expansion of the founder cells. This cytoskeleton remodeling intertwines with auxin signaling in the pericycle and endodermis in order for founder cells to acquire a basic polarity required for initiating lateral root development. Our results reveal the conservation of cell remodeling and polarization strategies between the Arabidopsis zygote and lateral root founder cells. We propose that coordinated, auxin-driven reorganization of the cytoskeleton licenses asymmetric cell growth and divisions during embryonic and post-embryonic organogenesis.
Gesehen am 05.09.2019